2020
DOI: 10.3136/fstr.26.59
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation of Mango ‘Ataulfo’ at Low Dose: Effect on Texture, Taste, and Odor Fruit

Abstract: Sensory descriptors of mango 'Ataulfo' treated with dose of γ-rad (Cobalt 60) of 0, 0.15, 0.30, and 0.45 kGys were evaluated. Eight trained panelists evaluated eleven sensory descriptors, three on taste, four on texture and four on odor. Judges found significant differences (P < 0.05) for sweetness, sourness, astringency, juiciness, firmness, mango odor and honey odor in at least one treatment. The principal component analysis revealed a positively association between juiciness, mango odor, and honey odor with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
2
4
0
Order By: Relevance
“…Very low irradiation doses (0.075 and 0.3 kGy) did not alter the content of glucose, fructose or sucrose in lemons, cucumbers, nectarines, pawpaws, persimmons, zucchinis or Ellendale mandarins. In agreement with the finding of the present study, Cancino-Vázquez et al 49 found that the difference in sweetness in mangoes detected by the panelists may be due to a higher proportion of sugars with higher sweetening power, such as sucrose and fructose, and a lower proportion of glucose in the non-irradiated fruit. In irradiated juice from this fruit, glucose content increased when doses of 0.5, 1.0, and 3.0 kGy were applied, but sucrose and fructose content increased only when doses of 3.0 kGy were applied.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Very low irradiation doses (0.075 and 0.3 kGy) did not alter the content of glucose, fructose or sucrose in lemons, cucumbers, nectarines, pawpaws, persimmons, zucchinis or Ellendale mandarins. In agreement with the finding of the present study, Cancino-Vázquez et al 49 found that the difference in sweetness in mangoes detected by the panelists may be due to a higher proportion of sugars with higher sweetening power, such as sucrose and fructose, and a lower proportion of glucose in the non-irradiated fruit. In irradiated juice from this fruit, glucose content increased when doses of 0.5, 1.0, and 3.0 kGy were applied, but sucrose and fructose content increased only when doses of 3.0 kGy were applied.…”
Section: Discussionsupporting
confidence: 93%
“…The least acidic samples were those treated with irradiation. Similar results were found by Cancino-Vázquez et al, 49 who found that rates given by panelists were lower for sourness in the case of irradiated fruits (0.15 and 0.30 kGy), although this difference did not correlate with the acid content in mango (mainly citric and malic acids), 51 with no difference between treatments in titratable acidity.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, in the Nayarit Coast, with the same mango variety, var Ataulfo, there were no statistical differences in the firmness of the fruits subjected to fertilized and unfertilized treatment (Nolasco- González et al, 2016). Cancino-Vázquez et al (2020) cite an inverse relationship between firmness and fibrousness in mango fruits var. Ataulfo, when treated with low dose of gamma irradiation on the Chiapas coast.…”
Section: Resultsmentioning
confidence: 99%
“…This is very significant, since the flavor in the fruits is the TSS content, they are also an estimate of the total sugar content, and in mango var. Ataulfo this characteristic is very attractive due to its high sugar content (Cancino-Vázquez et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The first Ataulfo mango tree grew in the municipality of Tapachula, located in the Soconusco region, in the state of Chiapas at south of the country in the border with Guatemala; therefore, this variety has had a designation of origin by the Mexican government since 2003 [4]. The positioning of this crop in national and international markets is related to the quality of the fruit, more specifically the pulp, since it has a high sugar content, low amount of fiber, aroma, sui generis flavor and long shelf life [5].…”
Section: Introductionmentioning
confidence: 99%